An analysis on cryptocurrency acceptance: a case study at bitcoin and other cryptocurrency forum / Ainin Sofiya Abdul Karim - Abdul Karim, Ainin Sofiya (Faculty of Business and Management, 2019)
The cryptocurrency adoption especially bitcoin has become phenomenal worldwide including Malaysia. A survey conducted by Luno shows that 57 percent from cryptocurrency users in Malaysia even have more than one bitcoin wallet. A huge demand from the market has drove several firms to launch Islamic cryptocurrency. Recently, a Malaysia-based firm HelloGold has received a shariah compliant certification from Amanie Advisors for its gold-backed cryptocurrency, GOLDX that was launched at the end of 2017. The number of cryptocurrency consumers keep on rising but the factor of what causing this rocketing number of users are yet to be a question. Series of research have been done to determine the prominent factors of what affecting the behavioural intention and user behaviour or called in some other journals as consumer adoption of cryptocurrency Mahomed (2017). Different research at different countries brought variety outcomes. Therefore the same study will be done throughout this research. A quantitative approach and two Multiple Regression will be used to test the existing theory proposed in Unified Theory of Acceptance and Use of Technology (UTAUT) on the acceptance of cryptocurrency.